Mozambique Economic Update, July 2017 : A Two Speed Economy - World Bank (World Bank, Washington, DC, 2017)
The third edition of the Mozambique Economic Update comes at a time when the economy is beginning to show some signs of recovery in 2017. But as extractives and other large industries drive the recent developments, whilst small and medium enterprises lag behind, Mozambique is increasingly showing the signs of being "A two-speed economy". Reestablishing macroeconomic stability through a more balanced mix of fiscal and monetary policy is a priority for private sector growth. Slowly easing inflation and lower credit levels suggest that the monetary policy cycle could begin to loosen as the economy continues to adjust. However, making this transition smoothly will require a sharper fiscal policy response to restore the health of Mozambique’s public finances.